Design and Implementation of Multi Agentbased Information Fusion System for Decision Making Support (A Case Study on Military Operation) - Arwin Datunaya Wahyudi Sumari; Adang Suwandi Ahmad (Journal of ICT Research and Applications, 2008)
Quick, accurate, and complete information is highly required for supporting strategically impact decision making in a Military Operation (MO) in order to reduce the decision cycle and to minimize the loss. For that purpose, we propose, design and implement a hierarchical Multi Agentbased Information Fusion System for Decision Making Support (MAIFSDMS). The information fusion is implemented by applying Maximum Score of the Total Sum of Joint Probabilities (MSJP) fusion method and is done by a collection of Information Fusion Agents (IFA) that forms a multiagent system. MAIFS uses a combination of generalization of Dasarathy and Joint Director's Laboratory (JDL) process models for information fusion mechanism. Information fusion products that are displayed in graphical forms provide comprehensive information regarding the MO's area dynamics. By observing the graphics resulted from the information fusion, the commandant will have situational awareness and knowledge in order to make the most accurate strategic de cision as fast as possible.